Synthesis and characterization of Al2TiO5 by Sol-Gel method - Hassan, F.; Majid, S.R.; Arof, Abdul Kariem (2009)
Al2TiO5 has been obtained by the sol-gel technique. Aluminum nitrate and titanium isopropoxide in required concentrations will dissolved in ethanol with citric acid as a nucleating reagent. The mixtures were reflux for 2h under continuous heating and stirring. The precursor obtained was then sintered in air at 1050 -c for 2h. The sintered products were characterized by X-ray diffractometer and Electrochemical Impedance Spectrosco y. To the highest room temperature is 4.02 x 10-9 S cm-1, which is exhibited by the sample containing 0.08 moles of aluminum nitrate and 0.02 moles of titanium isopropoxide.